Memajukan riset kesehatan mental di Indonesia: Integrasi nilai budaya, etik, dan ketelitian ilmiah - Listiyandini, Ratih Arruum (Konsorsium Psikologi Ilmiah Nusantara, 2025)
This article highlights the urgency of developing a mental health research ecosystem in Indonesia that combines cultural relevance, ethical process, and rigorous scientific methods. Despite the growth of mental health practices, few interventions in Indonesia are both evidence-based and culturally grounded. The author calls for structural support, cross-sector collaboration, and capacity-building to produce contextually relevant, evidence-based interventions rooted in local wisdom and contributing to the global body of mental health science.